Developing endurance - Reuter, Ben (Sport performance series, 2012)
Runners, cyclists, swimmers, rowers, triathletes, and ultradistance athletes must sustain performance at a high level to come out on top. Developing Endurance shows how to achieve optimal stamina to race your best through science-based aerobic, anaerobic, and resistance training. Written by 11 top experts in the National Strength and Conditioning Association, the top sport conditioning organization in the world, this guide provides both the background information and the exercises, drills, workouts, and programs for ultimate results. Athletes and coaches will appreciate the assessment tools, analyses, and instruction to define specific needs and establish effective training goals. Armed with these tools and information, you can create the ideal personalized training program for your sport and avoid lengthy plateaus while taking performance to the highest level.